ASSOCIATION OF ADRB2 GENE POLYMORPHISM WITH MORPHOFUNCTIONAL ALTERATIONS IN PATIENTS WITH HYPERTROPHIC CARDIOMYPATHY - S. M. Komissarova; N. N. Chakova; E. V. Krupnova; E. P. Mikhalenko; N. V. Tchebotareva; S. S. Kruglenko; A. A. Arabey; A. G. Mrochek (Евразийский Кардиологический Журнал)
Objective. Analysis of a clinical picture and functional dysfunctions with ADRB2 gene molymorphism in patients with PHCM. Materials and methods. 89 patients with PHCM were included in the study (69 males and 20 females, mean age 46,7±15,7), among which 56 had been diagnosed with the obstructive form, 33 patients had a non-obstructive form of the disease. The control set included 104 healthy donors adequate in age, and gender with PHCM. The clinical picture of the disease was assessed, echocardiographic indicators and daily ECG monitoring parameters were specified. The ADRB2 gene polymorphism analysis was made in all patients. Results. The association of the clinical picture, structural and functional LV myocardial peculiarities with ADRB2 gene polymorphism in patients with PHCM. It was revealed that the combination of Arg16rg/Gln27Gln genotypes is a risk genotype and is associated with the appearance of adverse clinical manifestations of the disease. The combination of Gly16Gly/Glu27Glu genotypes is protective and is Conclusion. The results obtained have revealed the association of the ADRB2 gene polymorphism with clinical, structural and functional dysfunctions in patients with PHCM which will allow making prognoses of adverse clinical manifestations risk and improving β-adrenoblocker treatment of PHCM patients.